2013
DOI: 10.1111/jpim.12110
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Adaptivity in Service Development: The Case of Mobile Platforms

Abstract: Together with the developing technologies of a fast-evolving Web environment, computers, and handheld devices, human-computer IntroductionI nformation is the absolute means for social beings to improve themselves, control the environment, and organize their relations with nature and other people. However, with today's fast-evolving technologies and Internet environment, information is everywhere at any time. The challenge is obtaining useful information and dealing with that information with the utmost eas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 77 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…Using a variety of different settings, previous studies have demonstrated that different e-SQ dimensions affect consumers' attitudes toward Web sites. For example, attitude has been partially influenced by privacy (Wolfinbarger and Gilly, 2003;Van Noort et al, 2008), system availability (Elliott and Speck, 2005), responsiveness (Wu, 2005) and efficiency (Basoglu et al, 2014;Loureiro, 2014;Van Noort et al, 2008). Therefore, this study expands such research to the telecommunication sector in an emerging market, revealing that a specific set of e-SQ dimensions influences customers' attitudes toward the telecommunication companies' Web sites.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Using a variety of different settings, previous studies have demonstrated that different e-SQ dimensions affect consumers' attitudes toward Web sites. For example, attitude has been partially influenced by privacy (Wolfinbarger and Gilly, 2003;Van Noort et al, 2008), system availability (Elliott and Speck, 2005), responsiveness (Wu, 2005) and efficiency (Basoglu et al, 2014;Loureiro, 2014;Van Noort et al, 2008). Therefore, this study expands such research to the telecommunication sector in an emerging market, revealing that a specific set of e-SQ dimensions influences customers' attitudes toward the telecommunication companies' Web sites.…”
Section: Discussionmentioning
confidence: 81%
“…Luo and Lee (2011) used the Taiwanese airline industry to conclude that perceived usefulness plays a main role in enhancing customers' attitudes toward online shopping and their purchasing intention. More recently, Basoglu et al (2014) argued that three online service platform quality dimensions -ease of use, usefulness and personalization -directly influence customers' attitudes toward the platform. In the tourism sector, Loureiro (2014) pointed out that four components of Web site quality (i.e.…”
Section: E-sq and Attitude Toward The Web Sitementioning
confidence: 99%
“…Seneler et al [47,48] explored the adoption of online services. Basoglu et al [7], Daim et al [17], Kargin et al [30] and Phan et al [44] explored adoption of mobile services. We reviewed factors explored in these studies and developed a limited taxonomy for this exploratory research: Enjoyment e Refs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Dadfar et al, 2013) and different industrial contexts for architecture design (e.g. Basoglu et al, 2014;Yang et al, 2012;Tatsumoto et al, 2009). Platform lifecycle and transition.…”
Section: Detailed Analysis Of Research Topics By Different Perspectivesmentioning
confidence: 99%